Hidroksiapatit dari Tulang Ikan Tuna Sirip Kuning (Tunnus albacores) dengan Metode Presipitasi - Mutmainnah, Mutmainnah; Chadijah, Sitti; Rustiah, Wa Ode (Al-Kimia, 2017)
Indonesia as one of the biggest tuna fish produsers in the world, produce tuna fish bones large enough. Since tuna fish bone contain high calcium it is potentially to be the raw material of hydroxyapatite. Hydroxyapatite are inorganic compounds constituent of bones and teeth has the moleculer formula Ca5(PO4)3OH. Synthesis of hydroxyapatite can be done with precipitation method through tuna fish bone calcination process at the temperature 900°C for 5 hours to obtain calcium compounds in the form of calcium oxide. Calcium wich has been obtained added phosphoric acid 0,6 M with flow rate/rapid 1 mL/minute. Controlled synthesis process parameters are pH 10 of solution. Yield of hydroxyapatite generated after synthesis with of the precipitation time 12 hours are of 91.15%. hydroxyapatite product obtained was analyzed by FTIR(Fourier Transform Infrared) and XRD (X-Ray Diffraction). FTIR analysis indicate the presence of OH groups, PO4 and CO3. Based on the resulting diffraction of XRD analysis, crystallite size obtained each of 211.29 nm structure is hexagonal. Scherrer method was used to obtain crystallite size.